PENERAPAN FUNGSI-FUNGSI MANAJEMEN PADA PETERNAKAN AYAM BROILER (STUDI KASUS : PETERNAK PLASMA PT AS PUTRA 2 CIREBON) - Juliawan, Dandi; Whydiantoro; Nur, Hafni Rizanuddin (SEMINAR TEKNOLOGI MAJALENGKA (STIMA), 2023)
Broiler Chicken Farm is one of the business fields that is required to have good management so that maximum production results can be achieved. The purpose of this research is to find out how management functions are implemented in broiler chicken farms and to find out how production results are after the implementation of management functions in broiler chicken farms. The research location in this study was the location of the plasma farmer AS Putra 2 Cirebon in Bantarjati Village, Kertajati District, Majalengka Regency. The research method used in this research is descriptive qualitative with a case study approach. Collecting data by conducting in-depth interviews, observation and documentation. Data analysis techniques go through three stages, namely data reduction, data presentation and drawing conclusions and verification. The data validation technique used is source triangulation. The results of this study, namely the implementation of management functions on broiler farms at PT AS Putra 2 Cirebon consists of several scopes, namely the scope of PT AS Putra 2 Cirebon, the scope of production, the scope of broiler chicken farms, and the scope of plasma breeder cages. Each scope has implemented management functions properly including Planning, Organizing, Actuating and Controlling. The production results after implementing the management function are very good by obtaining an average production result with a Index Performance (IP) value of 415.5.